The effects of tracheal tube cuffs filled with air, saline or alkalinised lidocaine on haemodynamic changes and laryngotracheal morbidity in children: a randomised, controlled trial - Soares, S. M.F. [UNESP]; Arantes, V. M. [UNESP]; Módolo, M. P. [UNESP]; dos Santos, V. J.B. [UNESP]; Vane, L. A. [UNESP]; Navarro e Lima, L. H. [UNESP]; Braz, L. G. [UNESP]; do Nascimento, P. [UNESP]; Módolo, N. S.P. [UNESP] (Wiley, 2017)
We studied the effects of tracheal tube cuffs filled with air, saline or alkalinised lidocaine on haemodynamic changes during tracheal extubation and postoperative laryngotracheal morbidity in children. We randomly allocated 164 children aged 3–13 years undergoing general anaesthesia to one of four groups; tracheal tube cuffs filled with air (n = 41); saline (n = 41); alkalinised lidocaine 0.5% (n = 41); or alkalinised lidocaine 1% (n = 41). Intracuff pressure was monitored and maintained below 20 cmH2O. The mean (SD) increases in systolic blood pressure after tracheal extubation compared with before extubation were 10.9 (10.8) mmHg, 7.3 (17.7) mmHg, 4.1 (10.5) mmHg and 1.9 (9.5) mmHg in the air, saline, 0.5% and 1% alkalinised lidocaine groups, respectively (p = 0.021). The mean (SD) increases in diastolic blood pressure after tracheal extubation compared with before extubation were 3.9 (9.7) mmHg, 7.9 (14.6) mmHg, 0.7 (10.4) mmHg and 3.6 (6.9) mmHg in the air, saline, 0.5% and 1% alkalinised lidocaine groups, respectively (p = 0.019). The mean (SD) increases in heart rate after tracheal extubation compared with before extubation were 14.2 (7.6) beats.min−1, 15.5 (13.1) beats.min−1, 5.2 (9.6) beats.min−1 and 4.1 (6.6) beats.min−1 in the air, saline, 0.5% and 1% alkalinised lidocaine groups, respectively (p < 0.001). The incidence of sore throat 8 h after tracheal extubation was 22.0% in the air-filled group, 9.8% in the saline group, 4.9% in the 0.5% alkalinised lidocaine group and 2.4% in the 1% alkalinised lidocaine group, p = 0.015. We conclude that filling the tracheal tube cuff with alkalinised lidocaine-filled reduces the haemodynamic response to tracheal extubation and postoperative laryngotracheal morbidity in children.
Keywords: complications: sore throat; cuffed tracheal tubes; lidocaine paediatrics: airway management